Spatial cognition in the built environment relationship of passenger wayfinding to imageability and legibility of international airports in Southern Mindanao - Rodriguez, Roland Francis C. (2019)
Airports having the most global, yet placeless environment makes it difficult for a person to create a unique image to differentiate it from others. Also, Massive airports are spaces that have low legibility that makes it hard for a human to navigate. The study assessed if the statements above is similar in the local context by scrutinizing two international airports in Southern Mindanao, Francisco Bangoy International Airport in Davao and General Santos International Airport in General Santos. Imageability of the airport was assessed through an imageability perception survey that was given to the passengers of Francisco Bangoy International Airport and of General Santos International Airport. Then, the current state of the airport was scrutinized by using the quantifiable imageability parameters of Amos Rapoport. Legibility of the airport was assessed through Depthmap X analysis wherein the connectivity, integration, visibility, and depth of space of the airport terminals were gathered and analyzed. The results of the analysis shown that both Francisco Bangoy International Airport and General Santos International Airport have performed lower than the ideal intelligibility score. Wayfinding behavior of the passengers were gathered by using the wayfinding survey and passenger movement analysis. Wherein, wayfinding behavior is indeed affected by the imageability and legibility of space especially first-time users and passengers that rarely use the airport. Based from the results of the study, it is hard for passengers to create a mental image of the space because of the poor Imageability of both Francisco Bangoy International Airport and General Santos International Airport. Furthermore, legibility of space is also poor which caused lostness and disorientation to passengers inside the terminal. From the results of the study, a guideline in designing an airport was made to address the issues of passenger wayfinding, imageability, and legibility of international airports in Southern Mindanao.